2019
DOI: 10.1051/0004-6361/201834522
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering an evolutionary sequence of merger stages in infrared-luminous starburst galaxies atz∼ 0.7

Abstract: Based on optical/near-IR Magellan FIRE spectra of 25 starburst galaxies at 0.5 < z < 0.9, Calabrò et al. (2018) showed that their attenuation properties can be explained by a single-parameter sequence of total obscurations ranging from A V = 2 to A V = 30 towards the starburst core centers in a mixed stars and dust configuration. We investigate here the origin of this sequence for the same sample. We show that total attenuations anti-correlate with the starburst sizes in radio (3 GHz) with a significance larg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 156 publications
(183 reference statements)
2
21
0
Order By: Relevance
“…5.2) and none is Xray detected Jin et al (2018). Therefore, we speculate that the compact morphology in this very highly star-forming sample is a consequence of ongoing mergers, similarly to local ultra-luminous infrared galaxies (ULIRGs) (Soifer et al 2000;Juneau et al 2009) and high-z compact starbursts (Puglisi et al 2017;Calabrò et al 2019;Marrone et al 2018).…”
Section: Multi-wavelength Imaging and Morphologymentioning
confidence: 78%
“…5.2) and none is Xray detected Jin et al (2018). Therefore, we speculate that the compact morphology in this very highly star-forming sample is a consequence of ongoing mergers, similarly to local ultra-luminous infrared galaxies (ULIRGs) (Soifer et al 2000;Juneau et al 2009) and high-z compact starbursts (Puglisi et al 2017;Calabrò et al 2019;Marrone et al 2018).…”
Section: Multi-wavelength Imaging and Morphologymentioning
confidence: 78%
“…Veilleux et al 2002). At intermediate redshifts (z∼0.7), Calabrò et al (2019) observed an increasing incidence of SF clumps when moving above the MS relation, which might indicate a prevalence of merger-induced clumpy star formation toward higher sSFRs. At z∼2, the morphological dichotomy seen in the local Universe becomes much less pronounced, since the fraction of irregular and disturbed morphologies is generally high, and spread out quite uniformly across the SFR-M plane (e.g.…”
Section: Introductionmentioning
confidence: 87%
“…In order to test this interpretation, we analyzed the subset of 19 starbursts, with available HST images and in our redshift range, that were presented in Calabrò et al (2018) as representatives of off-MS systems at 0.5 < z < 0.9 above a M * of 10 10 M . We showed that this sample comprises a sequence of different evolutionary merger stages, which can be traced by the equivalent width (EW) of Balmer or Paschen lines, and by the total attenuation (A V,tot ) toward the center of the starburst core in a mixed dust and stars configuration (Calabrò et al 2019).…”
Section: Clumpiness Evolution During the Mergermentioning
confidence: 99%
“…In Fig. 14 we compare the clumpiness of this SB subset to A V,tot and the EW of Hα and Paβ lines, measured in (Calabrò et al 2019). In the first upper panel, we find no significant correlation between c and A V,tot , with a Spearman correlation coefficient R= −0.34 (p-value= 0.13) and angular coefficient of the best-fit line consistent with 0.…”
Section: Clumpiness Evolution During the Mergermentioning
confidence: 99%
See 1 more Smart Citation